1988
DOI: 10.1073/pnas.85.2.569
|View full text |Cite
|
Sign up to set email alerts
|

3T3 fibroblasts induce cloned interleukin 3-dependent mouse mast cells to resemble connective tissue mast cells in granular constituency.

Abstract: As assessed by ultrastructure, histochemical staining, and T-cell dependency, in vitro-differentiated interleukin 3-dependent mouse mast cells are comparable to the mast cells that reside in the gastrointestinal mucosa but not in the skin or the serosal cavity of the mouse. We now demonstrate that when cloned interleukin 3-dependent mast cells are cocultured with mouse skin-derived 3T3 fibroblasts in the presence of WEHI-3 conditioned medium for 28 days, the mast cells acquire the ability to stain with safrani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 20 publications
1
50
1
Order By: Relevance
“…In contrast to the mature connective tissue-type MCs in the peritoneum and ear tissue, for example, MCs derived by in vitro differentiation of bone marrow stem cells predominantly express GAG chains of CS type, although it has been reported that SCF stimulation of BMMCs can induce an increase in heparin synthesis (42). Consequently, the inactivation of SG is expected to have a much more profound effect on BMMCs than what was caused by the inactivation of NDST-2, because the lack of SG should affect both CS and heparin biosynthesis.…”
Section: Fig 3 Immunoblot and Expression Analysis Of MC Proteasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the mature connective tissue-type MCs in the peritoneum and ear tissue, for example, MCs derived by in vitro differentiation of bone marrow stem cells predominantly express GAG chains of CS type, although it has been reported that SCF stimulation of BMMCs can induce an increase in heparin synthesis (42). Consequently, the inactivation of SG is expected to have a much more profound effect on BMMCs than what was caused by the inactivation of NDST-2, because the lack of SG should affect both CS and heparin biosynthesis.…”
Section: Fig 3 Immunoblot and Expression Analysis Of MC Proteasesmentioning
confidence: 99%
“…BMMCs are readily generated by culturing bone marrow stem cells in the presence of IL-3 and can be induced to mature further by addition of SCF (41)(42)(43). Bone marrow cells were prepared from SG ϩ/ϩ and SG ϩ/Ϫ animals as well as from littermate SG Ϫ/Ϫ animals and were cultured together with WEHI-3B-conditioned medium as a source of IL-3.…”
Section: Effect Of the Sg Knockout On MC Granule Maturation-tomentioning
confidence: 99%
“…During co-culture with fibroblasts, immature mBMMCs develop a histochemical phenotype that is more similar to that of the mature MCs in the arthritic joint, due in part to increased expression of heparin-containing serglycin proteoglycans (30). The co-cultured mBMMCs also undergo granule maturation as evidenced by their marked increased granule accumulation of histamine and the exopeptidase carboxypeptidase A3 (32,33). In support of these data, the cell granules become electrondense at the ultrastructural level (34).…”
Section: Mast Cells (Mcs)mentioning
confidence: 99%
“…Maturation of BMMCs were evaluated by the surface expression levels of FcεRI and c-kit and by granule maturation based on the acidic Toluidine blue staining. A CTMC culture model was originally established through coculture of BMMCs with Swiss 3T3 fibroblasts [33,34]. We modified this culture method and obtained CTMC-like cultured mast cells using mitomycin C-treated Swiss 3T3 fibroblasts in the presence of Kitl (30 ng/mL) as previously described [12].…”
Section: Preparation Of Bmmcs and Ctmc-like Mcsmentioning
confidence: 99%